New solutions for horse shelters to connect to the equestrian paths - Gianluca Bambi; Massimo Monti; Matteo Barbari (Journal of Agricultural Engineering, 2013)
A rational and modern network of riding trails involves the building of specific structures for the horses according to the new needs of equestrian tourists. These shelters require appropriate technical models that today cannot be found easily in the Italian or foreign literature. Over the years this gap has led to the development of the practice “do it yourself”, following old techniques of construction, not able to meet the new demands of the market of horse tourism. This research has highlighted two different solutions that can meet the needs of tourists riding today, in accordance with the laws about the construction and the health part. These structures have been designed observing the principles of low impact, low cost, easy installation, complete reuse. Two kinds of structures have been planned. Temporary stay horse shelter: building to put in resting places of interest along the path (historic villages, monasteries, etc.), where it is possible to arrange the horses for a few hours and allow to the riders to make a careful visit of places of interest. Overnight stay horse shelter: structure to put in particular points where horses and riders can spend the night. A new type of horse barn with annexed feed storage and saddle room. The structure is dynamic, due to the possibility to change quickly the position of the horses (max 8 places).